2004
DOI: 10.1203/01.pdr.0000106314.99930.65
|View full text |Cite
|
Sign up to set email alerts
|

Fetal Growth Restriction Has Long-Term Effects on Postnatal Lung Structure in Sheep

Abstract: We have previously shown that fetal growth restriction (FGR) during late gestation in sheep affects lung development in the near-term fetus and at 8 wk after birth. In the present study, our aim was to determine the effects of FGR on the structure of the lungs at 2 y after birth; our hypothesis was that changes observed at 8 wk after birth would persist until maturity. FGR was induced in sheep by umbilicoplacental embolization, which was maintained from 120 d until delivery at term (approximately 147 d); birth… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

3
90
2
3

Year Published

2008
2008
2024
2024

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 111 publications
(98 citation statements)
references
References 36 publications
3
90
2
3
Order By: Relevance
“…Following 20 d of umbilicoplacental embolization, tissue density and alveolar size and number were unaffected. However when these animals were studied postnatally, tissue density was increased at 8 wk of age whereas at 2 years of age the IUGR lung had fewer, larger alveoli (10,11). This suggests that while no structural changes are present in fetal tissue, experimental IUGR may induce morphological changes later in life.…”
Section: Discussionmentioning
confidence: 95%
See 1 more Smart Citation
“…Following 20 d of umbilicoplacental embolization, tissue density and alveolar size and number were unaffected. However when these animals were studied postnatally, tissue density was increased at 8 wk of age whereas at 2 years of age the IUGR lung had fewer, larger alveoli (10,11). This suggests that while no structural changes are present in fetal tissue, experimental IUGR may induce morphological changes later in life.…”
Section: Discussionmentioning
confidence: 95%
“…In experimental studies, structural changes in the IUGR fetal lung have been reported that may underlie impaired lung function. For example, studies in sheep have found that IUGR results in fewer, larger alveoli with thicker alveolar septa, and therefore impaired blood-gas exchange, which persists into adulthood (10,11). Functionally, these structural lung effects in IUGR sheep are reflected by reduced lung compliance and increased chest wall compliance in sheep-changes that may compromise respiratory function (12).…”
mentioning
confidence: 99%
“…Other studies have demonstrated that normal lung development is critically dependent on the presence of appropriate oxygen tensions and nutrition (34), which are reduced in SGA fetuses. In both sheep (35) and rats (36), the reduced number of alveoli associated with IUGR at birth persisted into adulthood with no evidence of catch-up growth. Those data are in line with the finding that lung function at school age was reduced in prematurely born infants who had experienced IUGR as compared with genderand age-matched children born at term (37).…”
Section: Sga and Respiratory Morbiditymentioning
confidence: 96%
“…G.S. Maritz a montré, chez l'agneau de 8 semaines ayant souffert d'un RCIU, une diminution du nombre d'alvéoles avec un élargis-sement de celles-ci, persistant chez l'animal adulte [8]. D'autres études chez l'agneau ont également montré des anomalies des voies aériennes (trachée et bronches) chez les animaux porteurs d'un RCIU [9].…”
unclassified